(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The article is on the new data about taxonomical status of the endemic species Betula borysthenica Klokov, which is listed in The Red Book of Ukraine. The data were obtained by chemotaxonomic, morphological and molecular genetic approaches. Based on the results of gel-electrophoresis of soluble seed storage proteins and morphology of seedlings some isolation of B. borysthenica from other taxa are shown. The application of two genetic markers – noncoding spacer sequence of ITS1 from nuclear genome and partial sequence of plastid gene rbcL, which are usually used for DNA-barcoding, showed no significant differences for distinguishing different taxa. The taxonomical status of B. borysthenica remains under discussion now.